Corrosion inhibition of copper with octadecylphosphonic acid (ODPA) in a simulated indoor atmospheric environment. (November 2021) - Zhao, Weijie; Chang, Tingru; Leygraf, Christofer; Johnson, C. Magnus
Abstract: The corrosion inhibition of self-assembled octadecylphosphonic acid (ODPA) layers on non-oxidized and pre-oxidized copper and Langmuir-Blodgett deposited ODPA layers on pre-oxidized copper was investigated under a simulated indoor atmospheric corrosion environment containing 80% RH and 100 ppb formic acid. The corrosion process was monitored in-situ with infrared absorption/reflection spectroscopy, and the corrosion products were further characterised by grazing incidence X-ray diffraction. Nano-FTIR microscopy was used to reveal the nature, size, and distribution of the corrosion products on the nanoscale. The combination of pre-formed cuprite and ODPA layers, both with only some nanometres thickness, provided an excellent protection under this environment. Data availability: The raw/processed data required to reproduce these findings cannot be shared at this time as the data also forms part of an ongoing study. Highlights: Octadecylphosphonic acid (ODPA) works as corrosion inhibitor under an indoor atmospheric corrosion environment. The formation of corrosion products was monitored in-situ. Nano-FTIR microscopy reveals the nature of the corrosion products on the nanoscale. An excellent corrosion protective behaviour was found on pre-oxidized copper deposited with ultrathin ODPA layers.